Tridecagonal Triangle

Geometry Level 3

Let vertices A A , B B , and C C of A B C \triangle ABC coincide with the first, third, and ninth vertices of a regular 13 13 -gon, respectively.

If cos A cos B + cos C = p q r \cos A - \cos B + \cos C = \frac{\sqrt{p} - q}{r} for positive co-prime integers p p , q q , and r r , find p + q + r p + q + r .

Inspiration


The answer is 18.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Sep 21, 2019

The angles are A = 6 13 π A = \tfrac{6}{13}\pi , B = 5 13 π B = \tfrac{5}{13}\pi and C = 2 13 π C = \tfrac{2}{13}\pi . If we write z = e 2 π i 13 z = e^{\frac{2\pi i}{13}} , then cos A cos B + cos C = 1 2 ( z 3 + z 3 + z 9 + z 9 + z + z 1 ) = 1 2 ( z + z 1 + z 3 + z 3 + z 4 + z 4 ) \cos A - \cos B + \cos C \; =\; \tfrac12\big(z^3 + z^{-3} + z^9 + z^{-9} + z + z^{-1}\big) \; = \; \tfrac12(z + z^{-1} + z^3 + z^{-3} + z^4 + z^{-4}\big) Note that z z is a root of X 13 1 = 0 X^{13}-1=0 which is not equal to 1 1 , and hence 0 = z 6 j = 0 12 z j = z 6 + z 6 + z 5 + z 5 + z 4 + z 4 + z 3 + z 3 + z 2 + z 2 + z + z 1 + 1 0 \; = \; z^{-6}\sum_{j=0}^{12}z^j \; = \; z^6 +z^{-6} + z^5 + z^{-5} + z^4 + z^{-4} + z^3 + z^{-3} + z^2 + z^{-2} + z + z^{-1} + 1 If we define α = z + z 1 + z 3 + z 3 + z 4 + z 4 β = z 2 + z 2 + z 5 + z 5 + z 6 + z 6 \alpha \; = \; z + z^{-1} + z^3 + z^{-3} + z^4 + z^{-4} \hspace{2cm} \beta \; = \; z^2 + z^{-2} + z^5 + z^{-5} + z^6 + z^{-6} then it is easy to show that α + β = 1 α β = 3 \alpha + \beta \; = \; -1 \hspace{2cm} \alpha\beta \; = \; -3 and hence α , β \alpha,\beta are the roots of the quadratic X 2 + X 3 = 0 X^2 + X - 3 = 0 , and moreover α > 0 > β \alpha > 0 > \beta . Thus we deduce that α = 1 2 ( 13 1 ) \alpha = \tfrac12(\sqrt{13}-1) , and hence cos A cos B + cos C = 1 2 α = 1 4 ( 13 1 ) \cos A - \cos B + \cos C \; = \; \tfrac12\alpha \; = \; \tfrac14(\sqrt{13}-1) making the answer 13 + 1 + 4 = 18 13 + 1 + 4 = \boxed{18} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...